Sistem Otomatis Penyimpanan Data Pendeteksi Fase Pelanggan Tegangan Rendah - Anang Dasa Novfowan; Mochammad Mieftah; Slamet Nurhadi (Politeknik Negeri Malang, 2024)
Inaccurate phase detection due to manual data recording often led to errors, impacting load balancing processes in electrical distribution. This research aimed to develop an automated phase detection system for low-voltage customers, utilizing a MicroSD-Card for data storage to reduce human error and enhance data reliability. The device used Power Line Carrier (PLC) communication technology integrated with customer identity (ID PEL) and employed Arduino Uno for phase data processing. The research method involved designing and testing phase detection and data storage functions across various distances to assess system accuracy. Findings indicated the system accurately detected customer phases and stored data efficiently, with minor delays only at longer distances. This automated solution effectively minimized manual errors in phase data entry. Future applications of this system could significantly improve load balancing accuracy and data management in electrical distribution networks